Early Re- Laparoscopy in Suspected Bile Duct Injuries after Laparoscopic Cholecystectomy - Ghimire, Roshan; Maharjan, Dhiresh; Thapa, Prabin (Birat Journal of Health Sciences, 2021)
Introduction: Management of patients with suspected bile leak or bile duct injury after laparoscopic cholecystectomy is challenging. Early laparoscopy in these groups of patients will benefit in terms of diagnostic as well therapeutic purpose. Objective: This study is done to assess utility of early re-laparoscopy in suspected bile duct injury in early postoperative period following laparoscopic cholecystectomy. Methodology: It is a descriptive study of all consecutive patients who underwent diagnostic as well therapeutic re-laparoscopy when required in suspected bile duct injury in early postoperative laparoscopic cholecystectomy that is within 72 hours of presentation. Study was conducted over a period from June 2019 to December 2020 at Kathmandu medical College, Sinamangal, Kathmandu, Nepal. Relaparoscopic operative findings and therapeutic intervention done were recorded. Result: The mean age at presentation was 34.6 years and male to female ratio was 1:1.8. During the study period, eleven patients underwent re-laparoscopy out of which one had no bile leak. Six out of ten were managed definitely in the same time of re-laparoscopy. However, four patients underwent definitive biliary reconstruction as they had already undergone arteriography in CT scan. Conclusions: Early re-laparoscopy may be beneficial prior to detail radiological investigations in suspected bile leak patients. Early re-laparoscopy can be an effective diagnostic as well therapeutic tool; and also it can help in planning for definitive repair in later date.